2020
DOI: 10.3390/ijerph17218038
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining and Supporting Seniors’ Wellbeing through Foreign Language Learning: Psycholinguistics of Second Language Acquisition in Older Age

Abstract: This study concerns aspects of positive psychology connected to foreign language learning (FLL) in an older healthy generation. The positive psychology perspective stresses the positive aspects of improved wellbeing in participants who engage in various activities, particularly mental and brain-training practices. Therefore, the aim of this study was to explore older people’s subjective feelings connected to their FLL as one of the crucial ways to improve their quality of life (QoL). The objective of the resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
(60 reference statements)
1
19
0
Order By: Relevance
“…The findings of this study reveal that the questionnaire statements on the basis of their meaning can be divided into four thematic groups: Intellect, Travelling and future, Positive emotions, and Purpose and motivation. The most consistent variable in both groups (Czech and Polish) were Positive emotions, which confirms our assumption that elderly people study a foreign language because it brings them happiness and personal satisfaction, which, consequently, positively affects their overall wellbeing (Pikhart & Klimova, 2020). In addition, the findings show that the Polish respondents assessed the positive effects of FLL in all four thematic categories significantly higher than the Czech respondents.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The findings of this study reveal that the questionnaire statements on the basis of their meaning can be divided into four thematic groups: Intellect, Travelling and future, Positive emotions, and Purpose and motivation. The most consistent variable in both groups (Czech and Polish) were Positive emotions, which confirms our assumption that elderly people study a foreign language because it brings them happiness and personal satisfaction, which, consequently, positively affects their overall wellbeing (Pikhart & Klimova, 2020). In addition, the findings show that the Polish respondents assessed the positive effects of FLL in all four thematic categories significantly higher than the Czech respondents.…”
Section: Discussionsupporting
confidence: 82%
“…The research into various aspects of foreign language learning (FLL) is ample, however, there is a significant impact of FLL on maintaining or even enhancing cognitive parameters in older adults as well (Klimova, 2018 ; Klimova et al, 2016 ; Phenniger et al, 2018 ; Pikhart & Klimova, 2020 ; Valis et al, 2019 ). The natural aging process is connected to many psychological and mental aspects and one of them is the process of cognitive decline, well documented by numerous research (Murman, 2015 ; Salthouse, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as many recent studies reveal, e.g., [8,[28][29][30][31][32][33], learning a foreign language seems to be an efficient tool for enhancing the overall well-being of older people, despite the fact that their learning outcomes are poor. The reason is that learning a foreign language brings them subjective feelings of happiness, satisfaction and positive motivation and thus positively affects their mental health and expands their social networks.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the research showed that it was partly through the stimulation of social well-being that the cognitive effects of FLL might be observed. In summary, FLL can be potentially used as a useful and efficient tool to maintain or improve subjective feelings of happiness and thus improve the quality of life in the participants of these courses (Pikhart and Klimova, 2020 ). From the perspective of psycholinguistics, FLL stimulates particular brain areas that are connected to cognitive function and this stimulation has proved beneficial.…”
Section: Introductionmentioning
confidence: 99%